Family Social Practices in Child Marriage in Bogor Regency, Indonesia - Nurul Amirah; Ekawati Sri Wahyuni; Tin Herawati (Sodality: Jurnal Sosiologi Pedesaan, 2025)
Child marriage remains an urgent social issue, particularly in Bogor Regency. This study aims to analyse the structural dimensions at the family level that play a role in child marriage in Kertajaya Village, Rumpin Subdistrict. The research employs a quantitative approach supported by qualitative methods, including in-depth interviews, observations, and descriptive statistical analysis. The sample consists of 90 women who married before the age of 19 in the past 10 years, selected through purposive sampling. The study compares the anti-speaker (aspek) and doyan speaker (dospek) communities. This practice is driven by low levels of education, economic constraints, and strong cultural and social norms. Men generally marry at an older age due to financial readiness, while women are often encouraged to marry young to preserve family honor. Child marriage is seen as a symbol of family honor and an economic strategy to maintain morality and reduce household financial burdens. Families play a central role, with fathers often making key decisions and mothers providing emotional support to children. Cultural and religious norms legitimize this practice, resulting in ‘kawin siri’. This study highlights the dual role of families as guardians of tradition and potential agents of change.